INTERPERSONAL COMMUNICATION PATTERNS AND COMMUNICATION BARIERS TO ROLEPLAY COUPLES ON SOCIAL MEDIA - Tri Wahyu Retno Ningsih; Farah Nasya Adani (Journal of Digital Media Communication, 2022)
This study aimed to find patterns of interpersonal communication and communication barriers that occur in role-play pairs on Twitter. This study uses a qualitative descriptive research method. The research informants were three pairs of role players. The results showed that three patterns of interpersonal communication occurred between the pair of role players, namely primary communication patterns, secondary communication patterns, and circular communication patterns. In interpersonal communication between the pair of role players, obstacles were found, namely misunderstandings in interpreting the message content, conflicts in relationships, obstacles caused by the network, and obstacles caused by the busyness of role-play players.